PENGAWASAN PENGELOLAAN LIMBAH CAIR PADA INDUSTRI PENGOLAHAN KELAPA SAWIT DI KABUPATEN BANYUASIN (Study Empiris : Kecamatan Tanjung Lago) - Dian Kristiawan; Siti Zubaidah (UNIVERSITAS ISLAM SYEKH YUSUF, 2020)
This study discusses environmental monitoring which is an activity carried out directly or indirectly by the regional environmental supervisory apparatus to determine compliance with business and / or activity compliance with regulations in controlling environmental pollution. This research method uses qualitative research using the theory proposed by T. Hani Handoko (1995: 23)